Rethinking Global Institutions in Environmental Protection: Guardians or Bystanders? - Maya Khater; Aishah Alkaabi; Enas Qutieshat; Maitha Alameri; Hamda Alkaabi (BESTUUR, 2026)
Global environmental degradation, driven by climate change, resource overexploitation, and rapid urban expansion, challenges the effectiveness of international institutions in functioning as genuine guardians rather than passive bystanders in environmental protection. This study critically examines the role of international organizations by analyzing their legal and institutional frameworks, evaluating their practical performance, identifying key implementation constraints, and formulating reform-oriented measures. The research applies a descriptive, analytical, critical, and inductive approach through a systematic assessment of international legal instruments, institutional practices, and relevant scholarly discourse. The study finds that environmental degradation continues to intensify despite the proliferation of international agreements, indicating a persistent gap between normative commitments and practical outcomes. Limited national capacities, weak coordination among international institutions, and the absence of effective enforcement mechanisms significantly undermine institutional effectiveness. Consequently, many international obligations operate at a formal level without achieving substantive implementation. The study concludes that strengthening international environmental governance requires comprehensive legal and institutional reforms that enhance compliance, improve coordination, and ensure effective enforcement of environmental obligations.